A stature-specific concept for uncemented, primary total hip arthroplasty - Omlor, Georg; Ullrich, Hannah; Krahmer, Knut; Jung, Alexander; Aldinger, Günther; Aldinger, Peter (Acta orthopaedica, 2010)
Background and purpose Variations in hip anatomy limit the femoral canal fit of standard uncemented hip stems. In addition, there are still issues with leg length discrepancy and offset reconstruction, potentially resulting in impingement, dislocation, and wear. Modular stems with different shapes for femoral canal fit and multiple neck options may improve the outcome and reduce complications. Patients and methods 173 patients (190 hips) received an uncemented THA with 1 of 2 different stem shapes for canal fit and a modular neck for stature-specific hip reconstruction. Median follow-up time was 9 (7-13) years. During the follow-up period, 20 patients died (22 hips) and 12 patients (13 hips) were lost to follow-up. 155 hips were available for evaluation, including clinical and radiological outcome. Results 1 stem was revised for a periprosthetic fracture following trauma; 10 cups and 2 modular necks were revised (1 for breakage and 1 during cup revision). At 10 years, stem survival was 100%, modular neck survival was 99% (CI: 95-100), and cup survival was 94% (CI: 87-97). No leg length discrepancies were measured in 96% of cases. Offset with anatomic lateralization was achieved in 98%. Median Harris hip score was 94 (47-100) and median Merle d'Aubigné score was 16 (10-18). Relevant radiolucent lines and osteolysis were not found. Interpretation The uncemented modular neck, dual-stem system used in this series allows accurate reconstruction of the joint by adapting the implant to the needs of the patient. This may improve the outcome of primary THA, which is supported by the results of this medium-term follow-up evaluation.
Gesehen am 14.06.2023